ILRI Information Services in support of livestock research in Africa - Sinha, P.K. (Pretoria University, 1997)
The International Livestock Research Institute (ILRI) is the newest among the international research centers supported by the Consultative Group on International Agricultural research (CGIAR). It has inherited mandates and resources of the two former livestock research centers of CGIAR, ILCA and ILRAD. Information management and the provision of information services form a vital element of ILRI's activities. The combination of ILCA and ILRAD information programmes is being used to develop an ingetrated global information service in support of livestock research. Both ILCA and ILRAD has established substantial information resources targeted at Africa. These resources, now part of ILRI, continue to serve Africa and are being further expanded to make them global in scope. The paper described ILRI information services oriented towards Africa. A special mention is made of the project of the former ILCA initiated to collect and conserve gray literature on livestock produced in sub-Saharan Africa and disseminate information among the potential users. A new information model developed and implemented by ILRI to provide support to global research on livestock is also described.